Effectiveness of Temperature and Drying Time on the Quality of Red Chili Powder (Capsicum annum L.) - Nursayuti Nursayuti; Hayatul Muna (Institut Pertanian Bogor, 2026)
The purpose of this study was to examine how temperature and drying time affect the quality of red chili powder. This study took place from December 6 to 21, 2023, at Almuslim Peusangan-Bireuen University's Mathematics and Natural Sciences Laboratory. This study used factorial RAL. There were two factors studied: temperature (S1 = 50°C, S2 = 60°C, and S3 = 70°C) and drying time (P1 = 5 h, P2 = 6 h, and P3 = 7 h). This study's findings include organoleptic tests, moisture content, and yield. The results showed that the temperature treatment at 70°C had a very significant effect on the moisture content of red chili powder, with a moisture of 7.91% and meeting the SNI requirements for dried chili moisture of 11%, but the treatment had no significant effect on the moisture of red chili, yield, or organoleptic test. The drying time treatment had no significant effect on the moisture content of red chili, the moisture content, the yield, and the organoleptic test; however, the 7-h drying time treatment had the highest percentage of the moisture content of red chili and red chili powder, as well as the lowest yield. The organoleptic test on red chili powder treated at 500°C with a drying time of 7 h had the highest color score, namely 3.68 an average score, and the highest aroma score, namely 3.58 with the category of quite like. Keywords: chili powder, drying time, red chili, temperature